Gaya Komunikasi Dakwah Nahi Munkar: Studi Netnografi Pada Akun Instagram @wajdi_azim - Kamila Rakhmawati; Pipir Romadi (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2026)
One of the other terms of the word da'wah is amar ma'ruf nahi munkar, which means to invite goodness and prevent evil. In the context of da'wah nahi munkar , there is a da'I who pursues the da'wah sector, namely ustadz Wajdi Azim who is active in preaching on social media, one of which is Instagram in @wajdi_azim account. Da'wah nahi munkar is indeed not as easy as imagined, so in conveying this message or material of da'wah nahi munkar, Ustadz Wajdi Azim experienced controversy with mad'u or Instagram users who failed to understand the essence of the da'wah nahi munkar that he did. Therefore, this study aims to analyze in a terotits, what communication style is used by Ustadz Wajdi Azim in conveying da'wah messages. This research uses two research methods, namely the qualitative method with a netnography study approach and the library reasserch method. The hail from this study shows that, in conveying the message of da'wah nahi munkar, Ustadz Wajdi Azim uses a controlling communication style and an analytical communication style, which is based on the four theories of communication style put forward by Carl Jung (1921)